Analisis Pemasaran dan Pendapatan Pedagang Bibit Sapi PO Kebumen di Pasar Hewan Argopeni Kecamatan Kebumen Kabupaten Kebumen: Analysis of Marketing and Income of Kebumen PO Cattle Breed Traders at the Argopeni Animal Market, Kebumen District, Kebumen Regency - Rohman, Miftakhu; Nuraeni, Nunur (Fakultas Peternakan Universitas Jambi, 2024)
Background: This study aims to determine the income of PO Kebumen cattle calf traders and their marketing flow at Argopeni Market, Kebumen District, Kebumen Regency. This study was conducted in July - August 2024 at the Argopeni Animal Market, Kebumen District, Kebumen Regency. Objectives: This study aims to determine the percentage of PO Kebumen cattle seed sales using blantik services and without blantik at the Argopeni Animal Market, Kebumen Regency, to determine the amount of income of PO Kebumen cattle seed traders at the Argopeni Animal Market, Kebumen Regency, and to determine the effect of the profile of PO Kebumen cattle seed traders as independent variables consisting of age, experience and education on income as dependent variables. Methods: This study is a descriptive study using a survey method using a questionnaire instrument in data collection. The sampling technique in this study used a census where the sample of PO Kebumen cattle seed traders was 20 people. The data analysis technique used to test the hypothesis is multiple linear regression analysis. Results: The results of the study showed the correlation coefficient of multiple linear regression for the income of PO Kebumen cattle seed traders at the Argopeni Animal Market, Kebumen District, obtained the following regression line equation: Y = 69563504.49 + -823614.803X1 + 513154.4409 X2 + -1925899.81 X3. Based on the Multiple R value of 0.419, there is a very strong correlation between age, experience and education with income. The results of the analysis of variance showed that the variables of age, experience and education had a significant effect (P>0.05) on the income of PO Kebumen cattle seed traders. The marketing channel for PO Kebumen cattle seeds at the Argopeni Animal Market that uses blantik services is 77.25% and those without blantik are 22.75%. The average income of PO Kebumen cattle seed traders at the Argopeni Animal Market, Kebumen is Rp. 21,423,500,-/month. Conclusion: Based on the Multiple R value of 0.419, it shows that there is no correlation between age, experience and education and income.